1990
DOI: 10.1073/pnas.87.3.1018
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of amino acids Asp-85, Asp-212, and Arg-82 in bacteriorhodopsin affects the proton release phase of the pump and the pK of the Schiff base.

Abstract: Photocycle and flash-induced proton release and uptake were investigated for bacteriorhodopsin mutants in which Asp-85 was replaced by Ala, Asn, or Glu; Asp-212 was replaced by Asn or Glu; Asp-115 was replaced by Ala, Asn, or Glu; Asp-96 was replaced by Ala, Asn, or Glu; and Arg-82 was replaced by Ala or Gln in dimyristoylphosphatidylcholine/3- [(3-cholamidopropyl)dimethylammonio]-l-propanesulfonate miceiles at pH 7.3. In the Asp-85 -Ala and Asp-85 --Asn mutants, the absence of the charged carboxyl group leads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
175
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(195 citation statements)
references
References 21 publications
(33 reference statements)
20
175
0
Order By: Relevance
“…Studies of the bR mutants have indicated that certain amino acids such as Asp-85, Asp-212, and Tyr-185, which are located in the proton channel near the Schiff base and involved in proton pumping, are also closely related to the regulation of the spectral transition of the purple membrane to the blue membrane (Mogi et af., 1988;Butt et al, 1989;Soppa et al, 1989;Otto et al, 1990;Subramaniam et al, 1990). As noted above, it appears that the color of bR is primarily regulated by a negative charge near the positively charged, protonated Schiff base (e.g.…”
Section: Color and Cationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of the bR mutants have indicated that certain amino acids such as Asp-85, Asp-212, and Tyr-185, which are located in the proton channel near the Schiff base and involved in proton pumping, are also closely related to the regulation of the spectral transition of the purple membrane to the blue membrane (Mogi et af., 1988;Butt et al, 1989;Soppa et al, 1989;Otto et al, 1990;Subramaniam et al, 1990). As noted above, it appears that the color of bR is primarily regulated by a negative charge near the positively charged, protonated Schiff base (e.g.…”
Section: Color and Cationsmentioning
confidence: 99%
“…This lysine, Lys-216, is therefore neutralized in the membrane, although the protonated Schiff base which it forms with the retinal is positively charged. Asp-85 has been suggested to act as a counterion to the protonated Schiff base Otto et al, 1990;Subramaniam et al, 1990), and its protonation probably leads to the formation of the blue membrane (see below). Jonas and Ebrey (1990) have proposed that the removal of a divalent cation from the bR active site Figure 1.…”
Section: Structurementioning
confidence: 99%
“…The absorption maximum of the retinal chromophore is believed to be primarily regulated by the electrostatic interactions between the charged or polar side chains of amino acids and the PSB, as well as certain carbon atoms along the retinal electronic system (10-14). From the structure (15) and genetic modification studies of bR (16,17), it has been found that Asp-85, Asp-212, and Arg-82 are charged groups in the retinal pocket. They are suggested to make a major contribution to the regulation of color of bR (17).…”
mentioning
confidence: 99%
“…Proton release involves a proton transfer from the Schiff base (SB) to Asp-85 (L → M) [42] (see step 2 of Fig. 13) and an almost simultaneous ejection of a proton into the outer medium [178]. This involves the initial movement of Arg-82 away from the active site due to proton transfer from the Schiff base to counterion Asp-85, and towards an extracellular proton release group [42] subsequently identified as Glu-194 and Glu-204 [48,49,68].…”
Section: Early Model Of the Br Proton Pump Mechanismmentioning
confidence: 99%